2012
DOI: 10.3109/13693786.2011.584913
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and biological features of catheter-associatedMalassezia furfurfrom hospitalized adults

Abstract: Malassezia furfur, an etiological agent of catheter-associated fungemia, requires long-chain fatty acids for in vitro growth. We examined the applicability of rDNA sequence analysis, autoaggregation testing in liquid culture, utilization of parenteral lipid emulsions, and phospholipase activity for discrimination of catheter-associated M. furfur strains. The rDNA sequence types of catheter-associated M. furfur strains were distinct from those of other isolates. All M. furfur isolates recovered from blood cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 28 publications
3
34
0
Order By: Relevance
“…Concerning the causative species, the presented data on Malassezia bloodstream infection isolates are in accordance with the findings of previous epidemiological surveys, unveiling M. furfur as the most common culprit agent . The occurrence of three cases of confirmed M. furfur bloodstream infection in a tertiary care hospital during a 2‐year period is consistent with the reported low prevalence of these invasive infections, usually confined to severely immunocompromised hosts .…”
Section: Discussionsupporting
confidence: 89%
“…Concerning the causative species, the presented data on Malassezia bloodstream infection isolates are in accordance with the findings of previous epidemiological surveys, unveiling M. furfur as the most common culprit agent . The occurrence of three cases of confirmed M. furfur bloodstream infection in a tertiary care hospital during a 2‐year period is consistent with the reported low prevalence of these invasive infections, usually confined to severely immunocompromised hosts .…”
Section: Discussionsupporting
confidence: 89%
“…However, conventional culture and identification methods offer the advantage of further evaluating the isolates for possible virulence factors, such as the production of phospholipase (44,170) and indole (108,184,336) and melanin synthesis (107). Furthermore, this was highlighted in a study by Akaza et al (6), in which the seasonal rates of isolation of Malassezia species from healthy skin determined by quantitative PCR (qPCR) were compared with those determined by use of Leeming-Notman agar (197).…”
Section: Resultsmentioning
confidence: 99%
“…The poor response to amphotericin B (112), is currently supported by the in vitro-recorded high MIC values of this agent (320). Recent data showed that the M. furfur strains that have the ability to cause systemic infections belong to a distinct internal transcribed spacer 1 group and demonstrate increased phospholipase activity (170).…”
Section: Malassezia In Systemic Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microscopic examination of clinical samples and colonies shows that small ovoid, ellipsoidal, or cylindrical blastoconidia (1.1 to 2.5 μm by 1.7 to 2.7 μm) with a large-base bud are characteristic of the genus Malassezia (2). Classical species identification comprises both biochemical and morphological studies, but this is rarely done due to the difficulty of interpreting lipophilic tests and the morphological closeness of the different species (1618). Insufficiency of species identification contributes to the lack of epidemiological knowledge about Malassezia infections.…”
Section: Introductionmentioning
confidence: 99%